Optimalisasi Referensi Karya Ilmiah Menggunakan Reference Manager - Edy Purwanto; M. Munir Syam AR (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2025)
Currently, universities face many challenges in society. Some of them are making people believe in the educational process offered by the university. Therefore, this service activity is very urgent to carry out. There were two issues raised in this activity, namely the students' weak knowledge of the reference manager and the issue of not knowing how to use the reference manager among students. This activity was carried out with the aim of providing education to students about the importance of reference managers and providing training on how to use Mendeley. This activity was held on Monday, 09 September 2024. There were 40 participants in this activity. Participants are students of the management study program, faculty of economics and business, Wiraraja University. The activities carried out are in the form of outreach and training. This method is deemed appropriate for solving problems experienced by management study program students at the economics and business faculty. The stages in this activity are the preparation stage, implementation stage and also the activity evaluation stage. From this activity, information was obtained that there was an increase in participants' understanding of reference managers, especially the Mendeley application. Next, it is necessary to assist the reference manager again by using another reference manager application.